Soundscapes of the Pernambuco New Cycle of Cinema - Araújo Porto, Igor; de Souza Rossini, Miriam (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2021)
This article explores Raymond Murray Schafer’s concept of “soundscape,” specifically in its relation and applicability to the discussion of the construction of space in cinema (Prysthon, 2017). We begin by reviewing the concept in Schafer (2001) and consider its pertinence to the study of sound design. Then, we investigate how the relation between soundscapes and sound design presents itself in the works of two successive generations of the Novo Ciclo de Cinema Pernambucano (Nogueira, 2009). Lastly, we point to ways in which those films represent the sounds of Northeastern Brazil, sometimes denying, sometimes identifying with the notion of the “invention of the Northeast,” advanced by Durval Muniz de Albuquerque Jr. (1993).